The Influence of Brand Equity Towards Purchase Decision (Case Study of Korean Cosmetics Innisfree in Jabodetabek) - Khairunnisa, Elisa Inten; Genoveva, Genoveva (Manajemen Bisnis Kompetensi, 2019)
The purpose of this study is to identify the influence of brand equity (brand awareness, brand association, perceived quality, and brand loyalty) towards consumer purchase decision using quantitative research. This quantitative research will evaluate the influence of brand awareness, brand association, perceived quality, and brand loyalty towards purchase decision of Korean cosmetics Innisfree in Jabodetabek, Indonesia. This research using t-test for testing partial level of 0.05, f-test for testing simultaneous influence to dependent variable, and coefficient of correlation (R) and determination (R2). This research is conducted in Jabodetabek, Indonesia using non-probability sampling which is convenience sampling and using 220 respondents as the sample. The result indicates that brand association, perceived quality, and brand loyalty have significant influence towards purchase decision while brand awareness have no significant influence towards purchase decision. Perceived quality become the strong influence variable towards purchase decision in this research. This research also indicates that brand awareness, brand association, perceived quality, and brand loyalty have simultaneous significant influence towards purchase decision with .730 of the adjusted R2.Keywords: Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty, Purchase Decision.